Optimalisasi Partisipasi Pemilih Pemula Pada Pemilu 2024 Di Desa Kadidia Kecamatan Nokilalaki Kabupaten Sigi - Juemi Juemi; Daniel T. Todapa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The service activities were carried out in Kadidia Village, Nokilalaki sub-district, Sigi Regency. This community service activity was carried out in September 2023. The number of participants was 31 people. This service is focused on the younger generation as Beginner Voters who have an important role in the general election (Pemilu) process. The results of this socialization and service aim to provide understanding to novice voters to be actively involved in the democratic party (election) and novice voters can have the knowledge to make choices and know the importance of elections in this nation's democratic journey. And secondly, you can make choices according to your conscience and can see the candidate's track record